A 70-Year-Old Woman with Metabolic Syndrome and Rapid-Onset Diabetic Neuropathy Complications: The Role Risk Factor of Age, Gender, Underlying Desease, Lifestyle, and Medication Adherence - Asmy, Hatimul; Noor Pratami, Gia; Rosita, Rita (Jurnal Ilmu Kedokteran Keluarga, 2024)
Diabetic neuropathy is a symptom or sign of nerve dysfunction in patients with diabetes mellitus. This condition may occur when blood glucose levels remain uncontrolled for an extended period and could be triggered by several risk factors. In this case, the patient's condition was identified at a primary healthcare center in Malang City. Both medical and non-medical histories were explored to determine the involved risk factors, followed by two home visits to further assess and identify additional risk factors. This case report highlights the role of the family medicine approach, where the interaction of biopsychosocial variables necessitates holistic and comprehensive therapeutic.